2019
DOI: 10.1016/j.toxicon.2019.06.220
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Nubein6.8 peptide isolated from the snake venom of Naja nubiae on melanoma and ovarian carcinoma cell lines

Abstract: This study was conducted to examine the cytotoxic effects of Nubein6.8 isolated from the venom of the Egyptian Spitting Cobra Naja nubiae on melanoma (A375) and ovarian carcinoma cell lines and to reveal its mode of action. The size of Nubein6.8 (6801.8 Da) and its N-terminal sequence are similar to cytotoxins purified from the venom of other spitting cobras. Nubein6.8 showed a high significant cytotoxic effect on A375 cell line and moderate effect on A2780. A clonogenic assay showed that Nubein6.8 has a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…During wound healing, a variety of cells such as inflammatory cells, fibroblasts, keratinocytes, endothelial cells, and growth factors as well as enzymes are involved (Velnar et al, 2009;Abdel-Ghani et al, 2019;Makvandi et al, 2019). The presence of other diseases such as DM impairs wound healing, demanding novel intervention to improve wound process by enhancing growth factor production, induction of angiogenesis, elevating collagen accumulation and macrophage function (Falanga, 2005;Campos et al, 2008).…”
Section: Wound Healingmentioning
confidence: 99%
“…During wound healing, a variety of cells such as inflammatory cells, fibroblasts, keratinocytes, endothelial cells, and growth factors as well as enzymes are involved (Velnar et al, 2009;Abdel-Ghani et al, 2019;Makvandi et al, 2019). The presence of other diseases such as DM impairs wound healing, demanding novel intervention to improve wound process by enhancing growth factor production, induction of angiogenesis, elevating collagen accumulation and macrophage function (Falanga, 2005;Campos et al, 2008).…”
Section: Wound Healingmentioning
confidence: 99%
“…Spheroids were obtained after seeding 5000 cells/well and were grown for three days. On the third day of spheroid growth, different concentrations of Doxo (20,50,75, and 100 μg/mL) and GA (10,20,40, and 60 μM) were added and the effects were monitored through transmission microscopy at 24 and 48 h. The scale bar is 200 μm and is the same for all images.…”
Section: Treatment Effect On Ht-29 Spheroid Morphologymentioning
confidence: 99%
“…After 3 days, the treatments with the Doxo and GA, either separately or in combination, were applied. Doxo alone was added in four concentrations (20,50,75, and 100 µg/mL), while GA alone was also added in four concentrations (10,20,40, and 60 µM). For the combined treatment, we two different GA concentrations were used (10 and 20 µM), each in combination with the other 4 Doxo concentrations.…”
Section: Treatment Of Ht-29 Spheroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent study reported Mambaquaretin-1 (peptide from green mamba venom), as a promising candidate for the treatment of polycystic kidney disease [ 39 ]. Another study described Nubein6.8, a peptide from the venom of N. nubiae , as a promising template for the treatment of human melanoma and ovarian cancer [ 40 ].…”
Section: Introductionmentioning
confidence: 99%